(untitled) (Journal of Hama University, 2024)
The research was conducted to find out the effect of the use of beta-glucans on the immune response in broilers, by using the hemagglutination-inhibition, where 200 Ross 308 hybrid chicks of both sexes and one age were used, and their initial weights were taken, and the chicks were raised together until the seventh day, then they were distributed randomly On four groups and in each group 50 chicks until the end of the experiment at the age of 42 days. And The control group (G1) was fed with the normal fodder mixture only, while the groups G2, G4, G3 were fed with the normal fodder mixture with Beta-Glucan added to it in the amount of 0.25 g/kg, 0.5 g/kg, and 1 g/kg of feed, respectively, from the age of 7 days until the age of 35. day of the experiment. Blood samples were collected on days 5, 28 and 38 of the experiment, where 7 birds were taken from each group after they were fasted for (4-6) hours, then weighed and blood samples were collected from the pterygoid vein and placed in plastic test tubes. The results showed an increase in the level of antibodies in blood serum in the beta-glucan groups compared with the control group. On the twenty-eighth day, significant differences were observed when comparing the criteria for specific immunological antibodies for Newcastle disease between the third group G3 (1.90) and the fourth group G4 (1.70) compared to the control group G1 (1.50) and the second group G2 (1.60), and on the thirty-eighth day, very high significant differences (0.01) (p < 0.01) were observed when comparing the criteria for specific immunoglobulins for Newcastle disease between the third group G3 (1.68) and the fourth group G4 (1.78) compared to the control group G1 (1.30) and the second group, G2 (1.30).The results at the age of 38 days indicated that there was an association in the rise of Newcastle antibodies with an increase in the concentration of globulins. The extracted results indicated the importance of using beta-glucans as feed additives due to the ability of these compounds to raise antibodies to Newcastle disease virus in broiler chickens.